Braiding Designs for Decolonizing Research Methodologies: Theory, Practice, Ethics - McGregor, Heather E; Madden, Brooke; Higgins, Marc; Ostertag, Julia (Reconceptualizing Educational Research Methodology, 2018)
Describing methodological design in decolonizing research as the intersection of theory, practice, and ethics, we share four focused micro-stories from our respective research projects. The metaphor of braiding represents the methodological design process within each of our research stories, significantly influenced by Dwayne Donald’s (2012) Indigenous métissage. Heather grapples with notions of reciprocity, Brooke considers the role of place in the construction of teacher identity, Marc engages with reworking photovoice, and Julia brings relationships with plants into her methodological design. Intentionally interrupting each other and ourselves, we feature the moments and movements of research design that are iterative, recursive, messy, and sometimes stuck, in contrast to the linear, untainted and dogmatic methodologies that assert themselves around us. Meanings and relationships may be produced in braiding our micro-stories together, exceeding what might be possible if they were presented separately. Readers may be invited into imagining the design of decolonizing methodologies beyond those we enacted.